Negotiating Power Relations in Cross-Cultural Communication: A Culture Studies Perspective on Swiss Leadership and Indonesian & Thai Employees at ATV Phuket - Djumari Putri, Dita Anggraini; Dwi Prasetyo, Bambang (Alphabet, 2025)
In multicultural organizations, power relations are not always overtly visible. According to Discursive Closure theory (Deetz, 1992), power is often exercised subtly through everyday communication practices, such as limiting opportunities to speak, controlling discussion topics, and shaping how messages are interpreted. This study analyzes how power relations are negotiated between Swiss leadership and Indonesian and Thai employees at ATV Phuket, a small-scale multicultural tourism company in Thailand. This study employed a qualitative case study approach to explore the lived experiences of participants, including the company owner, HR manager, permanent employees, freelance workers, and former staff. Data were collected through in-depth interviews and analyzed using thematic analysis. The theoretical framework was guided by Hofstede’s cultural dimensions (2010), Hall’s context culture theory (1976; 2000), and Deetz’s theory of discursive closure (1992). The findings of this study indicate that (1) the leadership adopts a high power distance approach despite originating from a low power distance culture, and (2) strategic decisions are centralized at the management level. Forms of discursive closure identified include disqualification (dismissing employee input), naturalization (framing policies as company norms), and meaning denial (rejecting the intended meaning of employees' messages). The contrast between the low context communication style of the leadership and the high context style of the employees intensifies power asymmetry and creates potential for miscommunication. The analysis reveals that power relations within small-scale multicultural organizations are continuously negotiated, yet they often benefit the party with stronger discursive control. This study contributes to the literature on culture studies and organizational communication by demonstrating how discursive closure operates within the context of cross-cultural workplace interactions.